2020
DOI: 10.1136/archdischild-2019-317991
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for collaborative research using very preterm birth cohorts

Abstract: ObjectivesTo develop research priorities on the consequences of very preterm (VPT) birth for the RECAP Preterm platform which brings together data from 23 European VPT birth cohorts.Design and settingThis study used a two-round modified Delphi consensus process. Round 1 was based on 28 research themes related to childhood outcomes (<12 years) derived from consultations with cohort researchers. An external panel of multidisciplinary stakeholders then ranked their top 10 themes and provided comments. In round… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“… 40 The second study identified education and the effect of minor impairments as being top research priorities. 41 Our definition of mild neurodevelopmental disabilities is in line with these recommendations. In comparison with the commonly used definition, this refined definition increased the proportions of children with mild disabilities but, interestingly, to a similar extent (around 5% to 7%) across gestational age groups.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“… 40 The second study identified education and the effect of minor impairments as being top research priorities. 41 Our definition of mild neurodevelopmental disabilities is in line with these recommendations. In comparison with the commonly used definition, this refined definition increased the proportions of children with mild disabilities but, interestingly, to a similar extent (around 5% to 7%) across gestational age groups.…”
Section: Discussionmentioning
confidence: 69%
“…In the first, general gross motor and cognitive abilities as well as sensory impairments were recommended for inclusion in a core outcome set 40. The second study identified education and the effect of minor impairments as being top research priorities 41. Our definition of mild neurodevelopmental disabilities is in line with these recommendations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Much less is known about parent priorities for preterm birth research across childhood. One recent study has focused on parent and other stakeholder priorities for childhood outcomes (Zeitlin et al, 2020). Through a Delphi process, Zeiltin and colleagues found that themes relating to the socioemotional needs of children and parents were most highly ranked across all stakeholder groups.…”
Section: Introductionmentioning
confidence: 99%